PENGARUH PENERAPAN METODE MIND MAPPING DALAM PEMBELAJARAN MENULIS CERPEN SISWA KELAS IX SMP NEGERI 2 SUPPA KABUPATEN PINRANG: The Effect of Mind Mapping Method in Learning to Write Short Stories in Grade Ix Students in Smp Negeri 2 Suppa Pinrang District - Ramadhan M, Agung; Salam; Nurhusna (Journal of Applied Linguistics and Literature, 2025)
" The Influence Of Applying The Mind Mapping Method In Learning To Write Short Stories For Class IX Students SMP Negeri 2 Suppa Pinrang Regency". This research aims to: (1) describe the results of writing short stories before and after applying the mind mapping method to class IX students SMP Negeri 2 Suppa, Pinrang Regency; (2) describe the effect of applying the mind mapping method in learning to write short stories for class IX students SMP Negeri 2 Suppa, Pinrang Regency. This research uses an experimental method with a one group pretest-posttest research design (single group initial test-final test). The results of the research show that classically students' pretest completeness scores can be said to be "not yet complete" with a completeness percentage of 31.81% with an average score of 66.28. For classical posttest scores, students' completeness scores can be said to be "complete" with a completeness percentage of 100% with an average score of 80.36. The significance value is 0.000 < 0.05, meaning that there is a significant influence on students' short story writing skills before and after applying the mind mapping method.